Dairy farm growth and the welfare impacts of a growth-based production quota on different farm size groups - Brand, Devin Lee (Kansas State University, 2021)
Low milk prices have led to divisive discussions of production controls as a potential solution among dairy farmers and industry groups. A growth-based production quota is one idea that has gained some support among farmers. The purpose of this thesis is to analyze the potential impacts of a growth-based production quota on different dairy farm size groups. To understand if small or large farms are growing faster, the relationship between a dairy farm’s initial size and their growth rate is analyzed. I use county-level information on the number of dairy farms and milk cows from the USDA’s Census of Agriculture. A statistically significant and positive relationship is found to exist between initial farm size and the growth rate in farm size over the past twenty years, which suggests that the larger a farm is, the faster they are growing their farm size and therefore milk production. Additional data from the USDA ARMS provides supporting evidence that larger dairy farms are growing at faster rates than smaller dairy farms in both 2000 and 2016. However, the difference in the growth rate was smaller in 2016 than in 2000. An equilibrium displacement model (EDM) is developed to estimate the impacts of a growth-based production quota. I consider scenarios where the production quotas range from requiring a 2 percent decrease in milk production to allowing for a 2 percent increase in milk production on each farm. Farms of all sizes are found to benefit in terms of producer welfare under all scenarios. Small farms benefit slightly more because they have smaller growth rates, but the difference between farm size groups is very small. Even when using very elastic estimates of the demand elasticity for fluid milk, all producer groups are found to benefit from the quota, though the benefit is much smaller. Under all the quota scenarios, the market price for fluid milk increases, therefore consumers are negatively impacted. Despite the benefits expected under the quota, some dairy farmers may still be opposed to a production control due to concerns over farm expansion potential, potential retaliatory trade actions by other countries, and potential consumer blowback due to higher market prices.
Keywords: Dairy farm growth; Dairy production control; U.S. dairy farms; Growth-based production quota